LADOBALA For Children in the Agronursing Area - Musviro Musviro; Iis Rahmawati; Nurul Hayati; Sri Wahyuningsih (Universitas Jember, 2023)
Optimal development is the goal that the child is expected to achieve during maturation which can be categorized into 5 domains, one of which is fine motor development. Fine motor development takes longer to achieve than gross motor development so it is necessary to stimulate one of them with a play approach. This study aims to analyze the development of LADO BALA play therapy (playdough Natural ingredients) on fine motor development and anxiety levels in children in the agricultural area. This research is a quasy experiment research with one group pretest-posttest design. The respondents in this study were 78 pre-school children with purposive sampling techniques. The measuring tools used in this study were DDST sheets to assess development and Faces Image Scale (FIS) to assess anxiety. The novelty in this study is that the media used is the result of the development of researchers, namely playdough with natural ingredients, namely wheat flour, salt, food coloring, warm water by utilizing local resources and wisdom in the agronursing area, namely using coconut oil which is safe and beneficial for children's skin health. The data obtained were analyzed with the Wilcoxon signed ranks test to determine the influence between variables. The results of each analysis were obtained namely p = 0.001 which stated that there was an influence of the development of playdough play on fine motor development and anxiety levels in children in the agriculture area. Playing lado bala facilitates children's development through squeezing, shaking, and increasing creativity in children, as well as making children feel happy so as to reduce anxiety in children.Playing ladobala can be one of the stimulations of fine motor development in pre-shool children in the agronursing area and ladobala media can be made by children with parents with easily available and safe materials.